2011
DOI: 10.1200/jco.2011.37.9677
|View full text |Cite
|
Sign up to set email alerts
|

Are Large Sample Size Studies the Answer to Evaluate Effects of Drug Use in Non–Clinical Trial Settings?

Abstract: TO THE EDITOR: We read with interest the article by Chang et al 1 published in a recent issue of Journal of Clinical Oncology. The authors used a new-user case-control study design that was expected to minimize prevalent user bias and improve the reliability of any significant findings. 2 However, we found at least three major flaws in their study design and data analysis that raised great concerns about their conclusions regarding the risk of cancer associated with the use of angiotensin II receptor blockers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Estimation of hazard ratios and 95% confidence intervals (CIs) of statin use during follow-up for cardiovascular disease (CVD) using a 1: 2 matched nested user-non-user cohort selected from the Hong Kong Diabetes Registry (refer to figure 1 for patient selection). users [19]. In response to a commentary on our report of reduced cancer risk in insulin users, we demonstrated the discrepant results using different analysis methods.…”
Section: Limitationsmentioning
confidence: 85%
See 2 more Smart Citations
“…Estimation of hazard ratios and 95% confidence intervals (CIs) of statin use during follow-up for cardiovascular disease (CVD) using a 1: 2 matched nested user-non-user cohort selected from the Hong Kong Diabetes Registry (refer to figure 1 for patient selection). users [19]. In response to a commentary on our report of reduced cancer risk in insulin users, we demonstrated the discrepant results using different analysis methods.…”
Section: Limitationsmentioning
confidence: 85%
“…The latter has been shown to be associated with RAS activation known to be associated with cancer development [15–18]. In the same study [8], the authors also reported increased cancer risk with other classes of antihypertensive drugs such as beta blockers, calcium channel blockers and thiazides with relative risks ranging from 1.15 to 1.32 [8], suggesting that drug indication rather than drug effects might explain these drug‐cancer associations [19].…”
Section: Biases and Potentials In Testing Effects Of Drug Usage On Camentioning
confidence: 90%
See 1 more Smart Citation
“…First, because the condition associated with drug use may contribute to the clinical outcome, for which the drug is prescribed to reduce risk, the propensity score for use of the drug is used to adjust for the drug indication [14]. Second, inclusion of existing users of drugs of interest will introduce prevalent user bias.…”
Section: Methodsmentioning
confidence: 99%
“…In a commentary, we pointed out that the Taiwan study had not adjusted for the propensity of use of ARBs either as a group or individually. We further used data from the HKDR to illustrate that the propensity score for ARB use as a group was independently associated with 13‐fold cancer risk compared with non‐ARB users . To this end, there is emerging evidence supporting the new roles of angiotensin II in inflammation, oxidative stress and ageing , all of which have been implicated in cancer development.…”
Section: Possible Mechanisms Linking Diabetes and Cancermentioning
confidence: 99%